Satyam Computers Ltd : Corporate Governance in Emerging Markets - Aggarwal , Monika (Gyan Management Journal, 2009)
It was one of the biggest corporate fraud in the history of India. Satyam Computers Services Ltd., the recipient of the Golden Peacock Award along with many other reputed honors, was renamed as 'Enron' of India, thereby, raising all brows on the trustworthiness of the Indian law , business processes, and business ethics. The family owned company had allowed others to chirp the professionalism of th Indian corporate by feeding investors shareholders, clients and employees a steady diet of asatyam. atyam was incorporated in 1987 as a private limited company providing software development and consultancy services. Ramalinga Raju and his brother Rama Raju ere the promoters of the company.
Keywords: corporate fraud; Computers Services Ltd; Golden Peacock Award; Enron